2020
DOI: 10.1111/acer.14432
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Transdermal Alcohol Monitors: A Systematic Review of Detection Validity, and Relationship Between Transdermal and Breath Alcohol Concentration and Influencing Factors

Abstract: Background: Research on alcohol consumption mostly relies on self-reported data, which are subject to recall bias. Wearable transdermal alcohol concentration (TAC) monitors address this limitation by continuously measuring the ethanol excreted via the skin. This systematic review aims to provide an overview of TAC monitors' reliability to detect alcohol consumption and methods to estimate breath alcohol concentration (BrAC) and number of standard drinks consumed in a given time frame. Methods: The databases ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 33 publications
2
44
1
Order By: Relevance
“…Similarly, for alcohol use intensity, day‐level correspondence between EMA and SCRAM ( r = 0.46) was modest, compared with person‐level correspondence ( r = 0.78). The person‐level correlation of 0.78 in alcohol use intensity between EMA and SCRAM slightly exceeds the reported correlation of 0.62 between TAC readings and self‐reports in a recent systematic review (van Egmond et al, 2020). In an alcohol administration study in a highly controlled laboratory setting, the correlation between transdermal and breath assessments of alcohol across 24 subjects was 0.84 (Sakai et al, 2006).…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Similarly, for alcohol use intensity, day‐level correspondence between EMA and SCRAM ( r = 0.46) was modest, compared with person‐level correspondence ( r = 0.78). The person‐level correlation of 0.78 in alcohol use intensity between EMA and SCRAM slightly exceeds the reported correlation of 0.62 between TAC readings and self‐reports in a recent systematic review (van Egmond et al, 2020). In an alcohol administration study in a highly controlled laboratory setting, the correlation between transdermal and breath assessments of alcohol across 24 subjects was 0.84 (Sakai et al, 2006).…”
Section: Discussioncontrasting
confidence: 63%
“…and TAC readings were correlated at 0.68 at the person-level (Rash et al, 2019). Similarly, a recent systematic review reported that TAC data from 3 biological detection methods (SCRAM, WristTAS, and Skyn) had a correlation of 0.62 with self-reported alcohol use (van Egmond et al, 2020).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…However, transdermal monitors surprisingly remain markedly underutilised in research investigating heavy drinking in public spaces, as well as in combination with other measures of intoxication and consumption. A recent systematic review by van Egmond et al [17] noted that ambulatory studies combining transdermal and EMA self-report measures have only assessed consumption amongst populations drinking a maximum of 12.4 standard drinks per week, the same amount an average festival patron will consume in a 24 h period [2]. Thus, there is a clear need to evaluate the combination of these measures among more heavydrinking populations and in a broader range of drinking contexts.…”
Section: Introductionmentioning
confidence: 99%